Helium Pickup Ion Velocity Distributions Observed in Interplanetary Coronal Mass Ejection Structures - Keiichi Ogasawara; Maher A. Dayeh; Robert W. Ebert; Berndt Klecker; Harald Kucharek (The Astrophysical Journal)
The velocity distribution functions (VDFs) of He ^+ pickup ions (PUIs) through two interplanetary coronal mass ejection (ICME) events associated with two interplanetary shocks are examined. Their specific properties in pitch-angle space were used as tracers of the local physical processes. These VDFs were studied using observations from the PLasma And SupraThermal Ion Composition instrument on board the Solar Terrestrial Relations Observatory with 10 minutes cadence and full energy and angular resolutions. The analysis focuses on pitch angle distributions and their average/deviation to evaluate heating/cooling, acceleration/deceleration, and pitch angle diffusion. For an ICME accompanied by the quasi-perpendicular shock, (a) reflected and energized particles were found in the upstream, and pitch angle scattering and suprathermal particle production were conspicuous in the downstream; (b) strong heating was observed in the sheath region; (c) suprathermal particles were found in the sheath region and attributed to the velocity fluctuation within the solar wind; and (d) universal pitch angle scattering was found throughout the ICME. For an ICME accompanied by a quasi-parallel shock, (a) localized heating and acceleration were found around the shock location; (b) power-law suprathermal tail distributions were found near the shock, suggesting diffusive shock acceleration processes; (c) weak or no sheath heating was observed; and (d) pitch angle scattering was correlated with magnetic field power spectral density. In the magnetic cloud for this event, pitch angle diffusion consistent with the scattering by counterpropagating Alfvén waves was found. This type of analysis can be applied to study shock injection processes and PUI transport/diffusion processes under active conditions.